Implementasi Sistem Perizinan Usaha Tambang Pasir di Sungai Batanghari Kab. Batanghari dalam Perspektif Hukum - Sayuti Sayuti (NALAR FIQH: Jurnal Hukum Islam, 2013)
On the one hand, indeed, can give a positive development for the advancementof the economic, social, cultural and so on. But on the other hand, developmentcan also have negative effects to people's lives. With regard to economicdevelopment efforts in the field of human resources management, these effortsare expected to be made in the form of environmentally friendly development.But the reality is not so, because many companies or industries that are not ableto provide benefits to the environment and even vice versa. This is where theactual main function of granting permittance to the authorities, because itpermit is a state administrative decision rendered pursuant to applicableregulations. Especially the business permittance system implementation sandmine in Batang Hari River, when viewed from a legal perspective, theimplementation of the permittance system is not yet fully run in accordance withthe legislation, because they found that the procedure has not been carried outproperly and not been determined by a specifically juridical basis regulate thepermittance issues.